2018
DOI: 10.3390/ijms19103082
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Cell Death Mechanisms in Major Neurodegenerative Diseases

Abstract: Neuronal cell death in the central nervous system has always been a challenging process to decipher. In normal physiological conditions, neuronal cell death is restricted in the adult brain, even in aged individuals. However, in the pathological conditions of various neurodegenerative diseases, cell death and shrinkage in a specific region of the brain represent a fundamental pathological feature across different neurodegenerative diseases. In this review, we will briefly go through the general pathways of cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
175
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(198 citation statements)
references
References 155 publications
2
175
0
Order By: Relevance
“…Necroptosis has been implicated in the development of some neurodegenerative diseases [74]. Alzheimer's disease (AD) is a degenerative brain disease and is characterized by the damage and loss of neurons.…”
Section: Necroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Necroptosis has been implicated in the development of some neurodegenerative diseases [74]. Alzheimer's disease (AD) is a degenerative brain disease and is characterized by the damage and loss of neurons.…”
Section: Necroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…They are typically characterized by abnormal proteostasis, where the cell is unable to maintain regulation of protein folding, translation, and degradation pathways. These defects in proteostasis lead to processes of cell death such as apoptosis and disrupted signaling mechanisms within the cell from oxidative stress, glutamate-mediated cytotoxicity, neuroinflammation, mitochondrial dysfunction, and increased endoplasmic reticulum (ER) stress [2][3][4][5][6][7]. However, the early factors involved in neuronal cell death are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal cell death is considered as a major hallmark of NDs. Neurotoxic molecules such as reactive oxygen species (ROS) and protein aggregates induce neuroin lammation or neuronal cell death, which eventually lead to neurodegeneration (Chi et al, 2018). Number of preclinical studies demonstrated the neuroprotective effects of crude extract or puri ied compounds of M. charantia by attenuating oxidative stress, neu-roin lammation and cell death.…”
Section: Neuroprotective Propertiesmentioning
confidence: 99%